Georgian კერა kera – Hebrew כיר kir “hearth” Georgian ქურა kura – Hebrew כו ר kur “furnace” - Lerner, Constantine B. (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The article discusses the origin of the Georgian words – kera (the fire place on earthen floor), kura (furnace with bellows for metal smelting) - from the Semitic roots.